1987
DOI: 10.1111/j.1751-1097.1987.tb04769.x
|View full text |Cite
|
Sign up to set email alerts
|

NEAR‐INFRARED DETECTION OF SINGLET MOLECULAR OXYGEN PRODUCED BY PHOTOSENSITIZATION WITH PROMAZINE and CHLORPROMAZINE

Abstract: A sensitive near‐infrared detection system has been used to study the steady‐state emission of 1O2 at 1268 nra produced by promazine (PZ) and chlorpromazine (CPZ) during photo‐illumination. Singlet molecular oxygen could be detected in a variety of ordinary and perdeuterated organic solvents, but was not detectable in water or deuterium oxide. The emission was enhanced in the perdeuterated organic solvents and could be eliminated by rigorous degassing or by addition of the singlet oxygen scavenger 2,3‐dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Although direct time-resolved detection of 1 O 2 in strongly light-scattering samples with multilamellar liposomes was too difficult to do using our germanium photodiode detector, results of such measurements in samples in which CPZ was solubilized in Triton X-100/D 2 O or dissolved in benzene, suggest that in hydrophobic environment CPZ is a relatively efficient generator of singlet oxygen. Similar conclusion was reached by Hall et al 19 and Roberts. 4…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although direct time-resolved detection of 1 O 2 in strongly light-scattering samples with multilamellar liposomes was too difficult to do using our germanium photodiode detector, results of such measurements in samples in which CPZ was solubilized in Triton X-100/D 2 O or dissolved in benzene, suggest that in hydrophobic environment CPZ is a relatively efficient generator of singlet oxygen. Similar conclusion was reached by Hall et al 19 and Roberts. 4…”
Section: Discussionsupporting
confidence: 89%
“…However, it has been shown that 1 O 2 is photogenerated by CPZ only in organic solvents. 19 It suggests that CPZ-dependent photoformation of singlet oxygen may also occur in membranes. It appears that not only CPZ itself but also its metabolites and photoproducts are able to generate reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty in the yields was ±5%. Singlet oxygen phosphorescence was detected as described previously ( , ). Perinaphthenone (Aldrich Chemical Co.) was used as a standard for the determinations of the singlet oxygen quantum yields.…”
Section: Methodsmentioning
confidence: 99%
“…Singlet oxygen generation. Generation of 1 O 2 by HA was confirmed experimentally by measuring the 1 O 2 phosphorescence spectrum as described previously (25,26). Briefly, the 1 O 2 phosphorescence measurements were performed in D 2 O using a broadband interference filter for HA irradiation; the light source was a 450 W Hg lamp.…”
mentioning
confidence: 99%